Noonan Plaza Apartments. The recovery of an Art Deco landmark in the Bronx - Marte Castillo, Jorge Aquiles (Entrópico Arquitectura y Urbanismo, 2023)
The rehabilitation of the built heritage and its close relationship with the collective memory acquire a special dimension when it positively affects the availability of social housing. This has been the case of the intervention carried out in the Noonan Plaza Apartments complex, one of the first works developed in the Art Deco style in Highbridge, in the Bronx County, in New York. This work designed by Horace Ginsberg and Marvin Fine and whose construction was completed in 1931 has been restored by Danois Architects, P. C. This firm scrupulously followed the restoration criteria established by the Landmarks Preservation Commission, for which it was recognized in 2022 with the Lucy Moses Award granted by the New York Landmarks Conservancy. This high-density housing complex has a sophisticated architectural plan, an impressive interior garden courtyard and a carefully designed envelope, which make it an example of good design at low cost. The rehabilitation updated the building's infrastructure to improve its energy efficiency, universal accessibility, and livability conditions, while recovering the urban image of an Art Deco architectural landmark in the Bronx. The article describes and analyzes the work, its relevance as an architectural landmark in New York and the restoration process carried out.